CURRENT-ALGEBRA OF SUPER WZNW MODELS - Abdalla, E.; Abdalla, MCB; Branco, OHG; Saltini, L. E. (Iop Publishing Ltd, 1994)
We derive the current algebra of supersymmetric principal chiral models with a Wess-Zumino term. At the critical point one obtains two commuting super-affine Lie algebras as expected, but, in general, them are intertwining fields connecting both right and left sectors, analogously to the bosonic case. Moreover, in the present supersymmetric extension we have a quadratic algebra, rather than an affine Lie algebra, due to the mixing between bosonic and fermionic fields; the purely fermionic sector displays an affine Lie algebra as well.